Vulnerability of information, on the Internet of Things - Najar Pacheco, José Custodio; Bohada Jaime, John Alexander; Alemán Novoa, Helena Clara Isabel (Ingeniería Solidaria, 2022)
Introduction: This article is a product of the review of the "Vulnerability of information, on the Internet of Things", developed from the Juan de Castellanos University Foundation in 2021. Methods: Review of articles and relevant literature on the exposure of information and some vulnerabilities in devices that are part of the Internet of Things (IoT). Results: Information, as one of the most valuable assets, is essential, which is why it is important to have technology, devices that are part of the IoT, despite vulnerabilities. Conclusions: Keeping information secure has become a challenge, because it is one of the most important assets of any organization. Its manipulation requires many actors and involves many factors, making it is difficult to control and protect. The constant emergence of technology and their applications in various fields, along with their relative ease of use and smaller sizes, have made significant inroads possible; we must accept that they are a part of the IoT. Originality: In the bibliographic review of the information, which results from the use of technology, how the IoT is vulnerable and even more so when it is configured with the Internet. Limitation: Technology is becoming more and more dependent on it, despite the vulnerabilities of IoT devices and the Internet.